A influência das famílias de origem na vida de um casal que passa por estressor econômico - Ciceri, Caroline (Universidade do Vale do Rio dos Sinos, 2014)
The influence of the origin families is an important point in the construction and formation of the couple, mostly when it faces stressors events like an economic bankruptcy. In this article it wants to demonstrate the usage of the Genogram as a tool in the Couple Therapy in order to identify the main goals: types of influences exercised by the origin family, mainly during a stressor event, limits and borders defined by the couple and transgenerational standards of family operation. A unique case study was realized with a couple in progresses in the Systemic Couple Therapy, which experienced an economic stressor moment. A construction of a trigenerational Familiar Genogram was realized with the couple, together with a specific interview proposed as a tool. Different influences exercised by the families were found, including financial and emotional ones, as well deficient borders which interfere in the couple autonomy and transgenerational standards repetition in the conjugal operation.
Keywords: Família de origem; Relacionamento conjugal; Transgeracionalidade; Origin family; Conjugal relationship; Transgenerationality